Applicability of Environmental Landscape Diagnostic Methodologies Based on GIS - Valero, Enrique; Álvarez, Xana; Picos, Juan; Abilleira, Fran (European Journal of Sustainable Development, 2016)
This work has shown that using a methodology that considers complex variables such as Visual Fragility and Visual Quality, gives the possibility to establish a zoning including the landscape factor in spatial planning processes. In addition, it has shown that it is possible to adapt this general methodology to the specific circumstances of the area. The proposed model allowed its application in large, mid-scale or even in particular cases by the modification of the scale at which the source variables are obtained. For the three areas of study, there have been simulated 600 points of view including a population of 152,500 fixed observers and a million of mobile observers, systematically reinforced by 300 viewshed of densification. The calculation of Visual Fragility Acquired by superimposing a large number of viewshed reduced the subjectivity and provided a great consistency to the results. With the consistent and comparable results in three areas, taking into account their differences in topography, morphology, land use and population pressure, indicated that the model could be applied in almost all the coastal area of Galicia. Keywords: geographic information systems, landscape planning, infrastructures effects